Material design consideration for gear component using functional graded materials - Al-Qrimli H.F.; Oshkour A.A.; Ismail F.B.; Mahdi F.A. (Inderscience Publishers, 2023)
Gears have numerous practical applications. It is an essential element for power transmission. It is used to increase or decrease the speed or change the direction of a power resource. When gears are operating, it will develop high stress concentration on the contact tooth surface. In practice most gear teeth fail due to surface contact, which is the most common failure. Selecting the ideal material for a gear tooth is significant for the purpose of operating gear system. This review study will increase additional understanding of ceramic functional graded materials (FGMs) and their applications and how these materials can solve the gear tooth surface problem. This study gives evidence that FGM is able to enhance the microstructure, mechanical properties of the gear and gives better hardness between two tooth surfaces. The conclusion will suggest a solution for the problem of contact surfaces in the gear tooth, by using functional graded materials. In the structure of FGM, the metal phase will provide strength to the gear tooth and the ceramic phase will augment the heat and wear resistance. 2015 Inderscience Enterprises Ltd.